The Effectiveness of Using Google Form Application as an Evaluation Tool for Islamic Education Learning at SDN 019 Mambu, Luyo District, Polewali Mandar Regency - Nasrah; Hamdanah; Kaharuddin; Firman; Usman (Universitas Muhammadiyah Palu, 2024)
This study explores the effectiveness of using the Google Form application as an evaluation tool for Islamic Education, Pendidikan Agama Islam (PAI), learning at SDN 019 Mambu, Luyo District, Polewali Mandar Regency. The research is motivated by instances where some students provided incorrect answers relative to the questions given during exams. The objectives are to (1) describe the process of using Google Form as an evaluation tool for PAI learning, (2) assess the implementation of PAI learning evaluation using Google Form, (3) identify factors that support and hinder the use of Google Form for PAI learning evaluation, and (4) propose strategies to address hindering factors in the use of Google Form for PAI learning evaluation. This research adopts a field research approach with a descriptive qualitative method. Data collection techniques include observation, interviews, and documentation. Data analysis follows Miles Huberman's approach, involving data reduction, data presentation, and drawing conclusions. The findings reveal that: (1) The utilization of Google Form as an evaluation tool for PAI learning at SDN 019 Mambu starts with preparing essential devices such as laptops and tablets, followed by formulating questions related to the learning materials. (2) Evaluation execution includes distributing question links, ensuring link functionality, and monitoring students' completion of the form. Pre-evaluation orientation and simulations are conducted to ensure students' familiarity with Google Form, showcasing its effectiveness in distributing questions, accessibility, and expeditious evaluation results. (3) Inhibiting factors encompass unstable internet connectivity, power interruptions, and delays among students in completing tasks. Meanwhile, supportive factors include the availability of Wi-Fi, iPads, and Chromebooks as school resources. (4) Mitigating measures to address these challenges involve providing internet data allowances to resolve connectivity issues and offering students opportunities to review and revise their responses. These efforts underscore the school's proactive approach in ensuring a seamless evaluation process for PAI learning.